The primary volcanic aerosol emission from Mt Etna: Size-resolved particles with SO2 and role in plume reactive halogen chemistry. (1st February 2018) - Roberts, T.J.; Vignelles, D.; Liuzzo, M.; Giudice, G.; Aiuppa, A.; Coltelli, M.; Salerno, G.; Chartier, M.; Couté, B.; Berthet, G.; Lurton, T.; Dulac, F.; et al.
Highlights: In-situ small sensor quantification of Mt Etna primary aerosol emission. Lognormal parameter fit finds trimodal primary aerosol, effective radius of 0.3 μm. Data analysis of real-time observations extracts molar sulfate/SO2 of 1–2%. Atmospheric model predicts OClO consistent with reported Mt Etna plume observations. Aerosol surface area–humidity dependence of young plume BrO-OClO chemistry predicted. Abstract: Volcanoes are an important source of aerosols to the troposphere. Within minutes after emission, volcanic plume aerosol catalyses conversion of co-emitted HBr, HCl into highly reactive halogens (e.g. BrO, OClO) through chemical cycles that cause substantial ozone depletion in the dispersing downwind plume. This study quantifies the sub-to-supramicron primary volcanic aerosol emission (0.2–5 μm diameter) and its role in this process. An in-situ ground-based study at Mt Etna (Italy) during passive degassing co-deployed an optical particle counter and Multi-Gas SO2 sensors at high time resolution (0.1 Hz) enabling to characterise the aerosol number, size-distribution and emission flux. A tri-modal volcanic aerosol size distribution was found, to which lognormal distributions are fitted. Total particle volume correlates to SO2 (as a plume tracer). The measured particle volume:SO2 ratio equates to a sulfate:SO2 ratio of 1–2% at the observed meteorological conditions (40% Relative Humidity). A particle mass flux of 0.7 kg s −1 is calculated for the measured Mt Etna SO2 flux of 1950 tonnes/day. A numerical plume atmospheric chemistry model is used to simulate the role of the hygroscopic primary aerosol surface area and its humidity dependence on volcanic plume BrO and OClO chemistry. As well as predicting volcanic BrO formation and O3 depletion, the model achieves OClO/SO2 in broad quantitative agreement with recently reported Mt Etna observations, with a predicted maximum a few minutes downwind. In addition to humidity – that enhances aerosols surface area for halogen cycling – background ozone is predicted to be an important control on OClO/SO2 . Dependence of BrO/SO2 on ambient humidity is rather low near-to-source but increases further downwind. The model plume chemistry also exhibits strong across-plume spatial variations between plume edge and centre.